Poétique/Politique de l'artifice dans Richard II - Pierre Iselin (Sillages Critiques)
This paper aims at relating two apparently distinct approaches to Richard II’s conspicuous degree of structural and stylistic sophistication. One is the historical and political context of Queen Elizabeth’s succession — a hot debate in which indirection may appear as a necessary political artifice, the other is the ostentatious and multiple use of poetic citation — mise en abyme of discourses and theatrical props, recurrence of symbolic and biblical motifs, insistence on poetic conceits and topoi, onomastics and wordplay. With its chiasmic architecture of inversion, Shakespeare’s play can be seen not only as the mannerist treatment of a medieval diptych, but also as a study in perspective, where meaning and reception are instable, roles liable to reversibility — a poetic reflection on the theatre of politics.